Revealed and reserved: a compensating approach of voluntary disclosure by family multinationals - Gu, Qian; Wang, Stephanie Lu; Bai, Tao (Journal of International Business Studies, 2024)
Family-owned MNEs (FMNEs) face unique challenges for their newly established foreign subsidiaries due to the information asymmetry and divergent demands between the controlling families and external stakeholders. Despite the significant theoretical and managerial implications, there has been a notable research gap in understanding how FMNEs strategically disclose information to overcome these challenges. Drawing from literature on firms’ stakeholder management and responses to institutional pressure, we propose that FMNEs seek a compensating approach to reconcile various stakeholders’ divergent needs, mitigate information asymmetry, and enhance legitimacy. The compensating approach encompasses both the content and amount of information disclosed. Specifically, FMNEs selectively conceal information sensitive to socioemotional wealth (SEW) to protect the core interests of the controlling families. Simultaneously, they voluntarily disclose more information to signal professionalization to external stakeholders, alleviating concerns associated with higher family involvement. We further argue that transparency pressure in FMNEs’ home context amplifies their utilization of compensating information disclosure. Our arguments are generally supported by analyzing 850 newly established foreign subsidiaries from both FMNEs and non-FMNEs between 2010 and 2017.